Persistence Property and Asymptotic Description for DGH Equation with Strong Dissipation - Ke-chuang Wang (Discrete Dynamics in Nature and Society)
The present work is mainly concerned with the Dullin-Gottwald-Holm (DGH) equation with strong dissipation. We establish a sufficient condition to guarantee global-in-time solutions, then present persistence property for the Cauchy problem, and describe the asymptotic behavior of solutions for compactly supported initial data.